Pengolahan Lindi Tpa Muara Fajar Dengan Proses Koagulasi Dan Membran Uitrafiltrasi - Megah Mulia Ginting; Jhon Armedi Pinem; Elvie Yenie (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Leachate is luquid which was produced from huge of waste at landfill. Leachate has organic substances which is potentially harmful of human and ecosystem. Because it can serve as a medium for the growth and development of  pathogenic microorganisms. This study aimed to determine the effect of coagulant  Aluminum Sulfate concentration in the coagulation-flocculation, membrane  resistance, flux and rejection percentages.  In the coagulation-flocculation process,  coagulant Aluminum Sulfate concentration was used 30 ppm. The process was done by quickly stirring in 200 rpm on 2 minutes and slow stirring in 60 rpm on 10 minutes with 30 minutes settling time of flocs. The precipitate formed and clear liquid were separated and the clear liquid was fed to the ultrafiltration membrane with variation of pressure at 1 bar, 1.5 bar and 2 bar.With 30 ppm coagulant the survey resulted was BOD5 reduced 25.00%, COD reduced 24.14% and TSS reduced 52.17%. After the membrane ultrafiltration process, the survey obtain the effective process is at 2 bar membrane pressure with number of rejection as following 71.43% of BOD5, 70.59% of COD  and 45.45% TSS. The fluks number is increasing align to pressure of membrane.   Keywords: Leachate, coagulation-flocculation, membrane  ultrafiltration,  Flux, rejection.